Internalized criticism and absence of care: separate pathways from childhood abuse and neglect to dual harm via self-compassion - Mao, Yanxia; Xie, Zhongguang; Zhang, Liying; Wang, Wenchao (Frontiers in Psychiatry, 2026)
BackgroundNon-suicidal self-injury and cyber aggression are increasingly prevalent among college students. Childhood maltreatment is a known risk factor for both behaviors, yet few studies have examined their co-occurrence (dual harm) or the underlying mechanisms from a developmental psychopathology perspective. This study investigates the distinct effects of childhood abuse and neglect on NSSI and cyber aggression, with self-compassion as a potential mediator.MethodsA longitudinal design with a six-month interval was employed. A sample of 2,301 Chinese college students completed the Childhood Trauma Questionnaire-Short Form and the Self-Compassion Scale at baseline, followed by the Inventory of Statements about Self-Injury and the Adolescent Cyber Aggression Scale at follow-up. Structural equation modeling and bootstrapping were used to examine direct and mediated pathways.ResultsChildhood abuse and neglect positively predicted both NSSI and cyber aggression. Negative self-compassion mediated the relationship between childhood abuse and both outcomes. For childhood neglect, positive self-compassion mediated its positive association with NSSI and cyber aggression, while negative self-compassion mediated a negative association.ConclusionsThe findings highlight differential pathways through which childhood abuse and neglect influence later self- and other-directed harm. Positive self-compassion may serve as a protective factor, whereas negative self-compassion may exacerbate risk. Tailored interventions focusing on enhancing self-compassion could help mitigate the long-term effects of childhood maltreatment.